Principles and practice of toxicology in public health - Richards, Ira S. (Ira Steven) 1948-; Bourgeois, Marie M. (Burlington, Mass. Jones & Bartlett Learning, 2014)
All public health professionals should have some level of knowledge of the basic principles of Toxicology. Whether dealing with issues as diverse as a workers' compensation claim for a job-related exposure and injury or the removal of toxic wastes from an urban community, public health professionals must be able to communicate with each other, the public, and our political leaders concerning how chemicals can, and the conditions under which they may, realistically produce harm. Principles and Practice of Toxicology in Public Health provides students with an understanding of the nature and scope of the discipline, so that they may be prepared to participate in a meaningful way in the often highly visible problem-solving and decision-making processes required of public health professionals. In four sections, it offers an introduction to the field, as well as the basics of toxicology principles, systemic toxicity, and toxicology practice. The text is immediately readable for the student with little technical background. The Second Edition is a thorough update that has been expanded with a new chapter on endocrine toxicology.
Toxicology and its roots as a science -- Chemical properties and information resources on hazardous chemicals -- Toxicity and the factors that modify toxic responses -- Biological poisons : plant and animal toxins -- Environmental pollutants and their fate -- Dose and response -- Absorption of toxicants and models of disposition -- Distribution, storage, and elimination of toxicants -- Biotransformation -- Chemical-induced mutagenesis -- Chemicals and cancer -- Role of the immune system -- Skin -- The liver and kidneys -- The cardiovascular system -- The respiratory system -- The nervous system -- The endocrine system -- The practice of toxicology -- Regulatory considerations -- Toxicity testing -- Uses and limitations of product labeling for public safety -- Toxicology principles in the management of acute poisonings -- Risk assessment and the perception of risk -- Making informed decisions.
Includes bibliographical references and index.
Keywords: Toxicology